Pengembangan Lembar Kerja Peserta Didik (LKPD) Elektronik Berbasis Project Based Learning (PJBL) Pada Pembelajaran IPAS - Dinda Dheffawwaz; Muhaiminah Jalal (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Thiis reiseiarch aiims to deiveilop an eileictroniic Studeint Worksheieit (Ei-LKPD) baseid on Projeict Baseid Leiarniing (PjBL) for Natural and Sociial Sciieinceis (IiPAS) leiarniing on thei human reispiiratory systeim mateiriial iin fiifth gradei studeints at SDN 250 Meirangiin. Thei study eimployeid Reiseiarch and Deiveilopmeint (R&D) usiing thei ADDIiEi modeil, whiich consiists of Analyzei, Deisiign, Deiveilopmeint, Iimpleimeintatiion, and Eivaluatiion stageis. Thei reisults show that thei deiveilopeid product meieits thei valiid criiteiriia baseid on eixpeirt valiidatiion. Meidiia valiidatiion achiieiveid 80% (valiid cateigory), languagei valiidatiion reiacheid 84.44% (veiry valiid cateigory), and mateiriial valiidatiion obtaiineid 82.60% (veiry valiid cateigory). Furtheirmorei, thei practiicaliity teist iindiicateid a veiry practiical cateigory, wiith teiacheir asseissmeint at 96.87% and studeint reisponseis at 96%. Theireiforei, thei PjBL-baseid Ei-LKPD iis feiasiiblei and practiical to bei useid as an iinnovatiivei teiachiing mateiriial that promoteis iinteiractiivei leiarniing, einhanceis conceiptual undeirstandiing, and deiveilops studeints’ criitiical thiinkiing skiills iin IiPAS leiarniing.